Legal Protection for Election Organizing Committees When They Experience Work Accidents During General Elections in the General Election Commission - Mirza Ghulam Rahmadipadma; Hananto Widodo; Widya Maya Sari (Universitas Negeri Surabaya, 2024)
This study focuses on the legal protection for election committee workers when they experience work accidents during general elections within the environment of the General Election Commission (General Election Commission or KPU). General elections are a cornerstone of democracy that determines the direction and leadership of a nation. In Indonesia, election organizers including the District Election Committee (Kecamatan Election Committee or PPK), Voting Committee (Positioning Committee or PPS), and Voting Organizing Group (Kelompok Organizing Pemulungan Pemulungan or KPPS) may face risks of accidents while performing their duties. This research utilizes normative research methodology, focusing on the study of legal documents and applicable regulations. The aim is to delve deeper into the legal aspects and protections that need strengthening to ensure the safety and well-being of election committee workers in carrying out their tasks. Considering the significant number of casualties during this democratic event, this study highlights the importance of health guarantees for these ad hoc bodies, which have not been sufficiently regulated in the Election Commission Regulations (Peraturan Election Commission General or PKPU). Additionally, the research examines the role of the Social Security Organizing Agency (Social Security Organizing Agency or BPJS) in providing social protection for election committee workers and the challenges faced in implementing employment social security at the regional level. The results underscore the need for policy improvements and increased collaborative capacity with relevant parties to conduct fair, transparent, and accountable elections that strengthen democracy in Indonesia.